Psicología y fin de vida - Barreto, Mª Pilar; Soler, Mª del Carmen (Psicooncología, 2003)
The aim of this work is to describe the main contributions of psychology to the field of End of Life Care. After basic questions that must be considered by all the interdisciplinary team, we put forth principles and tools for assessment and intervention strategies. We emphasize both the preventive and clinical role of Psychologists. We also consider counselling as the necessary frame for assessment and intervention. Moreover, specific strategies for concrete problems such as anxiety and depression are given. It is evident that psychology has an important role in this field; nevertheless, its recent involvement implies that more development of contributions is necessary. Further, we need to seek additional evidence regarding efficacy and efficiency of same.